The rise of Chinese military power, 1895-1912 - Powell, Ralph L. (Princeton legacy library., 1955)
A study of the growth of semi-personal Chinese armies and the rise of militarists to a position that permitted them to seize power upon the breakdown of the monarchic system. It traces the modernization of the land forces of the Chinese Empire and evaluates progress attained up to the establishment of the Republic in 1912. Ralph Powell is on leave from the history department at Princeton University as a professor at the National War College. Originally published in 1955. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905